2021
DOI: 10.1186/s12877-021-02448-8
|View full text |Cite
|
Sign up to set email alerts
|

Patient-centeredness in the multimorbid elderly: a focus group study

Abstract: Background  Patient-centeredness (PC) aims to adapt health care to the individual needs and preferences of patients. An existing integrative model of PC comprises several dimensions of PC which have not yet been investigated from the patients’ perspective. Older patients with multimorbidity represent a target group for patient-centered care, as their care needs are particularly complex and should be addressed individually. We aimed to assess the perspective that older patients with multimorbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
(52 reference statements)
0
4
0
2
Order By: Relevance
“…Das bedeutet, dass klassische Rollenzuweisungen in der geriatrischen Versorgungsrealität künftig deutlicher hinterfragt werden und – damit einhergehend – Zuständigkeiten weniger starr festgeschrieben sein müssen. Dieser Aspekt wird durch aktuelle Studien weiter untermauert, da in geriatrischen Versorgungskontexten alte Menschen ihre zunehmende psychophysische Vulnerabilität mit Blick auf Einsamkeit, steigende Symptomlast, Gebrechlichkeit und den damit verbundenen Autonomieverlust wahrgenommen und von Professionellen adressiert wissen wollen [ 10 ].…”
Section: Ausgangslage Und Hintergrundunclassified
See 1 more Smart Citation
“…Das bedeutet, dass klassische Rollenzuweisungen in der geriatrischen Versorgungsrealität künftig deutlicher hinterfragt werden und – damit einhergehend – Zuständigkeiten weniger starr festgeschrieben sein müssen. Dieser Aspekt wird durch aktuelle Studien weiter untermauert, da in geriatrischen Versorgungskontexten alte Menschen ihre zunehmende psychophysische Vulnerabilität mit Blick auf Einsamkeit, steigende Symptomlast, Gebrechlichkeit und den damit verbundenen Autonomieverlust wahrgenommen und von Professionellen adressiert wissen wollen [ 10 ].…”
Section: Ausgangslage Und Hintergrundunclassified
“…Diese Weitung des Teamverständnisses auch auf Berufsgruppen, die im geriatrischen Setting zusätzlich die für alte Menschen besonders wichtige soziale Perspektive einbringen, ist neu. Und das ist auch das innovative Moment im hier vorgestellten Modul „Der geriatrische Patient“, weil damit auch ein sektorenübergreifendes Denken und Handeln angeregt wird, das in der Realität der Praxis dringend gebraucht wird, wie dies auch in jüngsten Arbeiten bestätigt werden konnte [ 10 ].…”
Section: Diskussion Der Ergebnisseunclassified
“…Gender, grade, empathy, and communication skills were found to have statistically significant effects on dental students' attitudes regarding patient-centered services, which could be improved via a focus on enhancing empathy, emphasizing positive attitudes toward learning communication skills, and conducting patient-centered learning seminars ( 9 ). Furthermore, Kanat et al ( 10 ) found that the doctor-patient relationship and communication, doctors' characteristics, and patients' engagement were important determinants of PCC. Paiva et al ( 11 ) investigated the factors facilitating and inhibiting healthcare workers' implementation of PCC; they contended that the creation of an atmosphere that is conducive to communication, engagement of patients in medical decisions, and enhancement of medical personnel's ability to communicate effectively might foster the provision of PCC by medical workers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have linked PCC with various positive patient outcomes, including empowerment and engagement ( 10 , 12 ) favorable health outcomes, diminished socioeconomic, and racial disparities, shorter hospitalization periods and earlier discharge, and lower treatment costs ( 13 , 14 ). However, the existing literature on PCC has the following drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation